Peran Kejujuran Akademik (Academic Honesty) dalam Pendidikan Karakter Studi Pada Mahasiswa Jurusan Bimbingan Konseling Islam Fakultas Ushuludin Adab dan Dakwah Angkatan 2013/2014 - Fitri Sukmawati (The Pontianak State Institute of Islamic Studies, 2016)
Academic Honesty among students of the Department of Islamic Guidance and Counseling in the Faculty of Ushuludin Adab and Dakwa class of 2013/2014, there are still many who commit academic dishonesty or cheating. The causes of cheating behavior comes from the students themselves and the outside or external factors. For example, a lack of awareness and independence in learning among students as well as lazy behavior that is still part of the students’ personality. This behavior is a barrier to support character education that serves as educational goals.